NS1- and Minute Virus of Mice-Induced Cell Cycle Arrest: Involvement of p53 and p21(cip1) - Op De Beeck, Anne (American Society for Microbiology, 2001)
The nonstructural protein NS1 of the autonomous parvovirus minute virus of mice (MVMp) is cytolytic when expressed in transformed cells. Before causing extensive cell lysis, NS1 induces a multistep cell cycle arrest in G(1), S, and G(2), well reproducing the arrest in S and G(2) observed upon MVMp infection. In this work we investigated the molecular mechanisms of growth inhibition mediated by NS1 and MVMp. We show that NS1-mediated cell cycle arrest correlates with the accumulation of the cyclin-dependent kinase (Cdk) inhibitor p21(cip1) associated with both the cyclin A/Cdk and cyclin E/Cdk2 complexes but in the absence of accumulation of p53, a potent transcriptional activator of p21(cip1). By comparison, MVMp infection induced the accumulation of both p53 and p21(cip1). We demonstrate that p53 plays an essential role in the MVMp-induced cell cycle arrest in both S and G(2) by using p53 wild-type (+/+) and null (−/−) cells. Furthermore, only the G(2) arrest was abrogated in p21(cip1) null (−/−) cells. Together these results show that the MVMp-induced cell cycle arrest in S is p53 dependent but p21(cip1) independent, whereas the arrest in G(2) depends on both p53 and its downstream effector p21(cip1). They also suggest that induction of p21(cip1) by the viral protein NS1 arrests cells in G(2) through inhibition of cyclin A-dependent kinase activity.